The Development of an Instructional Material Book for Increasing the Effectiveness of the Learning Process in the Department of Religious Extension Education - Nababan, Andrianus; Sari, Agnes Novianti Permata; Manalu, Goklas J.; Lumban Gaol, Nasib Tua; Hutagalung, Tasya Ivana; Waruwu, Ariyanti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to develop an instructional material book for increasing the learning process's effectiveness in the religious extension education department. Religious extension education students at Institut Agama Kristen Negeri Tarutung participated in this research. This research method used research and development with the Borg and Gall Model, which, after being modified and adapted, consists of six stages, including (l) doing research and information collection; (2) planning; (3) developing a premier prototype; (4) conducting formative evaluation; (5) conducting product implementation; and (6) conducting summative evaluation. The validation process involved five experts assessing the content's material, media, design, evaluation, and language. Those experts were given questionnaires to evaluate the book's content, media, design, evaluation, and language appropriateness. Accordingly, the research results showed that the instructional material book about Christian religious extension and counseling techniques was feasible, proper, or valid to be used as an instructional material book in the Department of Religious Extension Education. Furthermore, according to the final test (post-test) of summative results carried out after the learning process using the book, the average student's overall score was 87.06, higher than the learning completeness score set at 75. Therefore, it was concluded that instructional material about Christian religious extension and counseling techniques was effective and helpful in enhancing students' knowledge and skills.